Globalization of industry : implications for developing countries beyond 2000 (UNIDO ViennaAT, 1996)
Addresses the growing concern that the increasing globalization of industrial production poses not only an opportunuty but also a potential threat to developing countries, who will be forced with mounting international competition in both their export and domestic markets as a result of the liberalization of world trade provided for in the Uruguay Round Agreements. Focuses on the particular risks posed by the changing international economic environment to the least developed countries' industrial development.
DC